Zebrafish as a model for acetylcholinesterase‐inhibiting organophosphorus agent exposure and oxime reactivation. Issue 1 (28th April 2016) - Koenig, Jeffrey A.; Dao, Thuy L.; Kan, Robert K.; Shih, Tsung‐Ming
Abstract : The current research progression efforts for investigating novel treatments for exposure to organophosphorus (OP) compounds that inhibit acetylcholinesterase (AChE), including pesticides and chemical warfare nerve agents (CWNAs), rely solely on in vitro cell assays and in vivo rodent models. The zebrafish ( Danio rerio ) is a popular, well‐established vertebrate model in biomedical research that offers high‐throughput capabilities and genetic manipulation not readily available with rodents. A number of research studies have investigated the effects of subacute developmental exposure to OP pesticides in zebrafish, observing detrimental effects on gross morphology, neuronal development, and behavior. Few studies, however, have utilized this model to evaluate treatments, such as oxime reactivators, anticholinergics, or anticonvulsants, following acute exposure. Preliminary work has investigated the effects of CWNA exposure. The results clearly demonstrated relative toxicity and oxime efficacy similar to that reported for the rodent model. This review surveys the current literature utilizing zebrafish as a model for OP exposure and highlights its potential use as a high‐throughput system for evaluating AChE reactivator antidotal treatments to acute pesticide and CWNA exposure.